General standards to define a Green City in China (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
According to this investigation, eco-cities are almost impossible to be realized, for several reasons. The concept of eco-city concerns mainly with "greenwashing". In our view, the main issue to consider for designing a sustainable city is to focus on the policies for planning and management at "district level". Human Settlements are usually considered sustainable, almost in equilibrium with the existing environment, when their size corresponds from 3.000 to 5.000 inhabitants. In China this number of inhabitants corresponds to the size of an average residential compound.Â